A new species of Cyrtodactylus Gray (Squamata; Gekkonidae) from the Thai Highlands with a discussion on the evolution of habitat preference - Grismer, L. Lee; Rujirawan, Attapol; Termprayoon, Korkhwan; Ampai, Natee; Yodthong, Siriporn; Wood, Perry L. Jr; Oaks, Jamie R.; Aowphol, Anchalee (Zootaxa, 2020)
A new gekkonid lizard, Cyrtodactylus maelanoi sp. nov., from Mae Hong Son Province of the Thai Highlands is described using an integrative taxonomic analysis based on morphology, color pattern, and the mitochondrial gene NADH dehydrogenase subunit 2 (ND2) and its flanking tRNAs. Phylogenetic analyses place the new species within clade 1 of the C. sinyineensis group and as the sister species to C. inthanon with an uncorrected pairwise sequence divergence of 3.9%. Collection data gathered in the field indicate that C. maelanoi sp. nov. is a habitat generalist. Reconstruction of the ancestral habitat preference for the C. sinyineensis group by way of stochasitc character mapping (SCM) indicates that karstic environments were the ancestral condition out of which the general habitat preference of the ancestor of C. maelanoi sp. nov. and C. inthanon and that of C. amphipetreaus and C. doisuthep evolved three times independently. Additionally, SCM demonstrated that the evolution of a granitic habitat preference from a karst-adapted ancestor happened in C. aequalis. The discovery of a new upland species in the Thai Highlands brings into focus the understudied nature of the mountain systems of western Thailand and the need for their continued exploration and conservation.